An Analysis of Volvo Cars’ Brand Experiences in Torslanda & the Alignment with World of Volvo - Hansson, Anton; Vatankhah Hansen, Nima (My University, 2023)
The aim of this report is to investigate how Volvo Cars can increase their overall brand equity through their brand experiences considering the imminent transformation where World of Volvo is launched, and the Brand Experience Centre is laid down. To accomplish this, the literature review first presents theory regarding the brand management field and the different sorts of brand equity. Then a framework is created to allow an appropriate analysis of the case study. Thereafter, a research question, including two sub questions, is formulated and a qualitative research strategy with an abductive approach chosen. The data is mainly collected through observations and semi-structured interviews with representatives from three identified key stakeholdergroups, namely the brand experience personnel, the onboarding team and the public affairs department. Initially, the current value generated by the different brand experiences is investigated before the changes which the transformation would entail are analysed. This is followed by an analysis and discussion concerning opportunities, potential value losses, affected stakeholders, and how challenges could be handled. The findings indicate that internal people are the ones that stand to lose on the transformation and recommendations are provided to the brand experience department regarding improvement potentials, how to mitigate risks, and how to ensure an enhanced overall brand experience for both internal and external people.
Keywords: brand equity; brand experience; EBBE; CBBE; customer satisfaction